Analisis Peran Pendidikan Orangtua Dalam Membesarkan Anaknya Berbasis Al-Qur’an dan Sunnah - Aida Efendi; Carina Septiani; Saidah Syakira; Zahra Dalvinova; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Every parent has an obligation to educate their children to become pious and pious children based on the Koran and Sunnah. Parents are also obliged to provide support to each child, to gain knowledge for the sake of happiness in this world and the hereafter. The aim of this research is to describe the responsibilities of parents in early childhood education according to Al-Maraghi's interpretation of Surah An-Nisa verse 9 and Surah At Tahrim verse 6. Apart from that, it is also to reveal the concept of the objectives of Islamic education regarding the educational role of parents in educating their children according to Al-Quran and Sunnah. The method used in this research is a qualitative method with a library research approach, data was obtained through basic information from the tafsir al-Maragh which contains the thoughts of Imam al-Maragh. Data analysis was carried out through the following stages: data processing (unification), data classification, data interpretation. The results of this research show; Firstly, Al-Qur'an Surah Al-Nisa verse 9 contains a warning to every parent that they will be worried and afraid if in the future they have to leave their child in a weak and helpless state. Second, parents are responsible for educating young children. The areas of education that are the responsibility of parents are physical and spiritual education, religious education, and character education.